On the connection between the transverse tubules and the plasma membrane in frog semitendinosus skeletal muscle - Zampighi, G (The Rockefeller University Press, 1975)
The transverse tubular system (TTS) of skeletal muscle fibers represents the morphological basis for the inward spread of conduction of the electrical signal that triggers muscle contraction. A historical account of the main steps contributing to the elucidation of the structure and function of the TSS has been presented by Huxley (1971). While the localization of the TSS and its association with the sarcoplasmic reticulum (SR) is well documented; there is still a need further to develop our knowledge of the morphology of the connection between the TSS and the plasma membrane. It is generally believed that the TSS opens directly to the extracellular space and that there is continuity between its membrane and the sarcolemma. However, direct observation of such a connection has been clearly shown only for the myotome of fish (Franzini-Armstrong and Porter, 1964). In other muscle fibers, only indirect evidence of the connection has been provided by experiments showing penetration of extracellular tracers into the TSS. These extracellular markers were also observed inside another membrane-bounded compartment consisting of round profiles named "caveolae" (Yamada, 1955) or "pinocytotic vesicles" (Ashurst, 1969). The present study deals with the communication between the TTS, caveolae, and plasma membrane (Peachey, 1965); Ezerman and Ishikawa, 1967; Schiaffino and Margreth, 1968; and Rayns et al., 1968). A detailed study of the caveolae compartment was undertaken with ruthenium red as an electron-dense tracer. As a result of this study, we propose that in certain species the caveolae compartment represents the transitional region in the connection between the TSS and the sarcolemma.